Application of intraoperative magnetic resonance imaging in large invasive pituitary adenoma surgery - Jie Li; Zixiang Cong; Xueman Ji; Xiaoliang Wang; Zhigang Hu; Yue Jia; Handong Wang (Asian Journal of Surgery, 2015)
Objective: To investigate the clinical application value of intraoperative magnetic resonance imaging (iMRI) in large invasive pituitary adenoma surgery. Methods: A total of 30 patients with large pituitary adenoma underwent microscopic tumor resection under the assistance of an iMRI system; 26 cases received surgery through the nasal–transsphenoidal approach, and the remaining four cases received surgery through the pterion approach. iMRI was performed one or two times depending on the need of the surgeon. If a residual tumor was found, further resection was conducted under iMRI guidance. Results: iMRI revealed residual tumors in 12 cases, among which nine cases received further resection. Of these nine cases, iMRI rescanning confirmed complete resection in six cases, and subtotal resection in the remaining three. Overall, 24 cases of tumor were totally resected, and six cases were subtotally resected. The total resection rate of tumors increased from 60% to 80%. Conclusion: iMRI can effectively determine the resection extent of pituitary adenomas. In addition, it provides an objective basis for real-time judgment of surgical outcome, subsequently improving surgical accuracy and safety, and increasing the total tumor resection rate.